HUBUNGAN POLA ASUH ORANG TUA DEGAN KEMANDIRIAN ANAK USIA PRASEKOLAH DI TK NEGERI PEMBINA MANADO - Mantali, Rizqa; Umboh, Adrian; Bataha, Yolanda B. (Universitas Sam Ratulangi, 2018)
Abstract: Independence in children is generally associated with the ability to do everything yourself, can measure the time of its own activities .The key to the success of a child’s independence is the pattern of parental care, parenting patterns affect the formation of child’s character. Parenting pattern of perents is divied into three, democratic parenting pattern, permissivea parenting and authoritarian parenting. This studi aims to determine the relationship of democratic parenting with the independence of children, the relationshipof permissive parenting with the independence of children and the relationship of parental authoritarian parenting with the independence of preschoolers. The design of this study using Cross Sectional approach, sampling techniques by total sampling is 58 childern. Instruments in this study from of questionnaires an analyzed using Chi-Squaretest statistic with a significance level of 95%.: α = 0,05. Chi Square test results with a significance level of 95% indicates that three is a relationship of parenting patterns of democratic and authoritarian parents with independence of preschoolers at Kindergarten of Pembina Manado Country, where the p.value of both is 0,001 and 0,011 samller than (α = 0,05). For Chi-Square test result on permissive parenting with a 95% : α = 0,05 significance level showed no relationship of permissive parenting pattern with independence of preschoolers at Kindergarten of Pembina Manado Country, where the p.value is greather than α = 0,05. Keywords: The Parenting Parents, Independence of preschoolers Abstrak: Kemandirian pada anak umumnya dikaitkan dengan kemampuan untuk melakukan segala sesuatunya sendiri. Kunci kesuksesan seorang anak menjadi mandiri salah satunya adalah pola asuh orang tua. Pola asuh orang tua berpengaruh terhadap pembentukan karakter anak. Tujuan penelitian ini untuk mengetahui hubungan pola asuh demokratis dengan kemandirian anak, hubungan pola asuh permisif dengan kemandirian anak dan hubungan pola asuh otoriter orang tua dengan kemandirian anak usia prasekolah di TK Negeri Pembina Manado. Rancangan penelitian ini menggunakan pendekatan cross sectional. Cara pengambilan sampel dengan cara total sampling yaitu sejumlah 58 anak. Instrumen penelitian ini berupa kuesioner dan dianalisa menggunakan uji statistik Chi- Square dengan tingkat kemaknaan 95%: α = 0,05. Hasil uji Chi-Square (X2) dengan tingkat kemaknaan 95% (α = 0,05), menunjukkan ada hubungan pola asuh demokratis dan otoriter orang tua dengan kemadirian anak usia prasekolah di TK Negeri Pembina Manado, dimana nilai p keduanya adalah 0,001 dan 0,011, lebih kecil dari α = 0,05. Untuk hasil uji Chi-Square (X2) pada pola asuh permisif dengan tingkat kemaknaan 95% (α = 0,05), menunjukkan tidak ada hubungan pola asuh permisif dengan kemandirian anak usia prasekolah di TK Negeri Pembina Manado, dimana nilai p= 0,056, lebih besar dari α = 0,05. Kata Kunci: Pola asuh Orang Tua, Kemandirian Anak Usia Prasekolah.